Voltage vector control of a hybrid three-stage 18-level inverter by vector decomposition - Kadir, M.N.A.; Mekhilef, Saad; Ping, H.W. (Institution of Engineering and Technology (IET), 2010)
This study presents a three-stage 18-level inverter design and its innovative control method. The inverter consists of a series-connected main high-, medium- and low-voltage stages. The high-voltage stage is made of a three-phase, six-switch inverter. The medium- and low-voltage stages are made of three-level inverters constructed by H-bridge units. The proposed control strategy assumes a reference input voltage vector and aims to operate the inverter in one state per sampling time to produce the nearest vector to that reference. The controller operates to reach the desired state with minimum switching actions, giving the priority in switching reduction to the higher voltage stage. The approach of the proposed control strategy has been presented, a set of related terms has been defined and the implementation process has been described. The test results verify the effectiveness of the proposed strategy and the capability of the inverter to produce low-voltage distortion and switching losses.